A comprehensive power-flow model of multi-terminal PWM based VSC-HVDC systems with DC voltage droop control. (November 2018) - Khan, Shagufta; Bhowmick, Suman
Highlights: Unified power flow models of integrated AC-MTDC systems employing PWM controlled VSCs have been presented. The modulation indices and the DC side voltages of the VSCs appear as unknowns in the power-flow models. Both linear and nonlinear DC voltage droop controls have been incorporated. Multiple case studies were implemented on the IEEE 300-bus test network. The convergence characteristics validate the robustness of the power-flow models. Abstract: This paper presents power-flow models of AC power systems integrated with voltage-sourced converter (VSC) based multi-terminal high voltage direct current (MTDC) grids. Pulse-width modulation (PWM) control is employed for the VSCs. In the proposed approach, the VSC modulation indices are considered as unknowns. For control of the MTDC grid, DC voltage droop control has been implemented. The proposed method includes both linear and nonlinear voltage droop characteristics. Converter losses are included in the proposed model. Depending upon the terminal end line active power specifications of the VSCs, two different voltage droop control models have been developed. The convergence properties in the proposed approach are found to be independent of the MTDC grid location, its topology, the MTDC control strategy employed and the operating point specification. Numerous case studies are carried out by applying different control modes to multiple topologies of MTDC grids embedded in the IEEE-300 bus test system. For all the case studies, the power-flow algorithms were implemented with MATLAB. In all occurrences, a mismatch error tolerance of 10 −10  p.u. was selected. The results validate the proposed work.